Social voices : the cultural politics of singers around the globe - Gibbs, Levi, 1980- (University of Illinois Press, 2023)
"Around the world and across time, singers and their songs stand at the crossroads of differing politics and perspectives. Levi S. Gibbs edits a collection built around the idea of listening as a political act that produces meaning. Contributors explore a wide range of issues by examining artists like Romani icon Esma Redžepova, Indian legend Lata Mangeshkar, and pop superstar Teresa Teng. Topics include gendered performances and the negotiation of race and class identities; the class-related contradictions exposed by the divide between highbrow and pop culture; links between narratives of overcoming struggle and the distinction between privileged and marginalized identities; singers' ability to adapt to shifting notions of history, borders, gender, and memory in order to connect with listeners; how the meanings we read into a singer's life and art build on one another; and technology's ability to challenge our ideas about what constitutes music. Cutting-edge and original, Social Voices reveals how singers and their songs equip us to process social change and divergent opinions"--